THE OCCURRENCE OF CODE SWITCHING ON PERSONAL MESSAGE OF BLACKBERRY MESSENGER - Tajudin (2013)
The study entitled "The Occurrence of Code Switching on Personal Message of BlackBerry Messenger" aims to investigate languages used in code switching on Personal Message of BlackBerry Messenger (PM of BBM), the types of code switching, and the reasons of BBM users in using code switching. This research involved 25 university students in Bandung as samples. The data were gathered through compiling the PM of BBM and distributing questionnaires. Several theories were applied to analyze the data, namely theory of switching types proposed by Poplack (1980), and theory of reasons of switching investigated by Hoffman (1991, in Tiana, 2009), and Savile-Troike (1986). The findings reveal that the users tend to use group of switched-languages (Indonesian-English) in code switching (80%). On the other hand, dealing with types of code switching appeared on PM of BBM, intersentential switching is the most dominant switching type (40.63%). Furthermore, the data analysis result from questionnaires found that most of the respondents (24%) stated that they did switching for real lexical need, which is the BBM users mostly used code switching on their PM because lack of equivalent lexicon. Keywords: code switching, Personal Message, BlackBerry Messenger, types, reasons Skripsi berjudul "Kemunculan Alih Bahasa pada Personal Message di BBM" ini bertujuan meneliti penggunaan bahasa pada proses alih bahasa di PM BBM, tipe alih bahasa yang muncul, dan alasan pengguna BBM menggunakan alih bahasa. Skripsi ini melibatkan 25 mahasiswa sebuah universitas di Bandung sebagai sample. Data yang didapatkan melalui pengambilan PM BBM dan pembagian kuisioner. Beberapa teori digunakan untuk menganalisa data, diantaranya teori mengenai tipe alih bahasa dari Poplack (1980), dan teori tentang alasan penggunaan alih bahasa dari Hoffman (1991, dalam Tiana, 2009), dan Savile-Troike (1986). Hasil penelitian menyatakan bahwa pengguna BBM cenderung menggunakan kelompok alih bahasa Indonesia-Inggris pada proses alih bahasa (80%). Sedangkan tipe alih bahasa yang paling dominan muncul di PM BBM adalah intersentential switching (40,63%). Selain itu, berdasarkan hasil kuisioner diperoleh hasil bahwa mayoritas responden (24%) menggunakan alih bahasa untuk alasan kebutuhan leksikal, yaitu mereka mayoritas menggunakan alih bahasa pada PM BBM karena tidak adanya padanan kata yag tepat yang dapat digunakan. Kata kunci: alih bahasa, Personal Message, BBM, tipe, alasan